2016
DOI: 10.1136/thoraxjnl-2015-207967
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of chemical pleurodesis in spontaneous pneumothorax recurrence prevention: a systematic review

Abstract: ObjectivesSpontaneous pneumothorax is a common pathology. International guidelines suggest pleurodesis for non-resolving air leak or recurrence prevention at second occurrence. This study comprehensively reviews the existing literature regarding chemical pleurodesis efficacy.DesignWe systematically reviewed the literature to identify relevant randomised controlled trials (RCTs), case–control studies and case series. We described the findings of these studies and tabulated relative recurrence rates or ORs (in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
72
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(75 citation statements)
references
References 62 publications
2
72
0
1
Order By: Relevance
“…Successful use of TPC has also been reported in PLCH, BHD, bronchiolitis obliterans, and Ehlers-Danlos Syndrome (97, 98). Blood patch pleurodesis, whereby a patients own blood is instilled through an existing chest tube, has emerged as an effective option for treatment for pneumothorax with reported pneumothorax recurrence rates of 15.6–18.2% (99). The advantage of this technique is the almost complete absence of typical pleurodesis-associated side effects such as pain and fever (100).…”
Section: Introductionmentioning
confidence: 99%
“…Successful use of TPC has also been reported in PLCH, BHD, bronchiolitis obliterans, and Ehlers-Danlos Syndrome (97, 98). Blood patch pleurodesis, whereby a patients own blood is instilled through an existing chest tube, has emerged as an effective option for treatment for pneumothorax with reported pneumothorax recurrence rates of 15.6–18.2% (99). The advantage of this technique is the almost complete absence of typical pleurodesis-associated side effects such as pain and fever (100).…”
Section: Introductionmentioning
confidence: 99%
“…Talcum powder is the most commonly used agent worldwide in inducing pleurodesis, and is considered to have the highest efficiency [20,21]. In a study by Yazicioglu et al comparing sericin with other pleurodesis agents, sericin pleurodesis was found to be superior in certain aspects when compared to talcum powder [4].…”
Section: Discussionmentioning
confidence: 99%
“…In Thorax , Halifax RJ,  et al 10 try to answer one of these questions. They undertook a systematic review of the effectiveness of chemical pleurodesis in spontaneous pneumothorax recurrence prevention.…”
Section: Introductionmentioning
confidence: 99%